Public health expenditure and economic growth in India: A causal analysis - Stephen, Geethu Rachel; Savitha, N. (The Economics and Finance Letters, 2025)
The causal relationship between public health spending and economic growth is investigated in this study. Data from a panel of 17 states in India is used for the period 2011 to 2022. The states are selected and categorized into three panels—most improved, moderately improved, and least improved—based on the incremental progress in the health index of the National Institution for Transforming India (NITI) Aayog to ensure homogeneity of the group. The Kao cointegration test and Granger causality tests are used for analysis. The cointegration test results showed a long-run equilibrium nexus between public healthcare expenditure and economic growth. In the panel of moderately improved states, the panel Granger-causality model found that there is a two-way causality between the variables. However, there is no causality in the most improved states. The least improved states exhibit a unidirectional causality from public health spending to economic expansion. This implies that the level of progress in the health index does not always correspond to the effectiveness of healthcare spending or its influence on economic growth.